The Impact of Europeanization on Minority Communities - Crepaz, Katharina; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden (Imprint), 2016)
Katharina Crepaz investigates how two-dimensional ('top-down' and 'bottom-up') Europeanization processes affect minority communities by using a comparative approach, encompassing cases from both "old" (pre-2004) and "new" EU member-states. The author thereby bridges two dichotomies made in the literature so far, and outlines how Europeanization takes place in non-acquis areas. She does so by looking at four very different case studies: the German-speaking minority in South Tyrol/Italy, the Bretons in France, the German minority in Silesia/Poland, and the Italian minority in Istria/Croatia. Contents Literature Review - Concepts of Europeanization Theoretical Background, Case Selection and Methodology Case Studies - Background and Analysis Comparative Process Tracing Analysis and Outlook Target Groups Scholars, Lecturers and Students of Political Science, Sociology and Law NGO and minority Organization employees, minority members, politicians in minority contexts About the Author Katharina Crepaz, Ph.D. is a post-doctoral research associate at the Max Planck Institute for Social Law and Social Policy as well as at the TU München. Her research interests include Europeanization processes, national and immigrant minorities in the EU, the Roma, transnational civil society, as well as processes of inclusion and participation regarding marginalized groups. <.
Literature Review - Concepts of Europeanization -- Theoretical Background, Case Selection and Methodology -- Case Studies - Background and Analysis -- Comparative Process Tracing Analysis and Outlook. .
Keywords: Comparative Politics; Public policy